Bratchenko O. V. Little known Russian romantic writer - Jakob de Balmen - Bratchenko O. V. (Philological Treatises, 2020)
J. de Balmen is an unknown Russian writer, the representative of Romanticism of the 30-s of the XIX century. T. Shevchenko dedicated “Kavkaz”, one of his most revolutionary poems, to him. There is only one monograph by A. I. Kuzmenko about his life and work called “An Unforgettable Friend…: The Story About Life and Creative Work of J. de Balmen”. Unfortunately, there is no analysis of the writer’s literary works in this monograph. The article deals with the general characteristics of J. de Balmen’s literary heritage and reveals the most important features of his creative manner.